Comparison of the Histologic Results of Atypical Glandular Cells-Favor Neoplasia and Atypical Glandular Cells-Not Otherwise Specified - Alper Karalök; Özgür Koçak; Tolga Taşçı; Bülent Yırcı; Işın Üreyen; Sevgi Koç; Taner Turan; Gökhan Tulunay (Medical Network, 2016)
Objective: Cervical cancer screening programs are widely performed in all around the world. The interpretation of the Pap smear test is a big challenge in gynecology practice particularly when associated with atypical glandular cells. In this study, we performed a retrospective analysis of cytologic results associated with atypical glandular cells in our institution. Material and Method: We retrospectively reviewed Pap smear tests resulted as "atypical glandular cells". A total of 122 women had screening tests reported as "atypical glandular cells" between 2003 and 2013 at the Ministry of Health, Etlik Maternity and Women's Health Teaching Research. The cytology reported as "atypical glandular cells" were evaluated in two main groups: Atypical glandular cells-favor neoplasia (AGC-FN) and atypical glandular cells-not otherwise specified (AGC-NOS) compared by means of histologic results. Results: Thirty-two women have been reported as AGC-NOS on cytologic examination and 90 women were defined as AGC-FN. There was no significant difference between AGC-FN and AGC NOS groups in terms of age. In AGC-FN group, a total of 13 women (13/90) (14.4%) had malignant histological diagnosis. In AGC-NOS group only one woman (1/32) (3.1%) was diagnosed as malignant. All the malignant cases in this study are older than 35 years. Conclusion: The incidence of AGC is less than 1% in all Pap smear examinations. Two main factors were important in the outcome of the AGC. The first one is the subgroup. AGC-FN group has a higher risk of malignancy. The second important factor is the age of the patient. To be older than 35 years old seems to increase the risk of malignancy.